Enhancing sales at twenty-one autos through consumer-centric design thinking - Lulu Lesmana; Danang Indrajaya; Arien Arianti Gunawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to increase sales at Twenty-One Autos by using a Design Thinking approach, chosen for its ability to deeply understand consumer needs and expectations. This approach is relevant for creating solutions that are more responsive to the challenges faced by consumers, with a focus on improving their satisfaction and experience, which directly impacts sales growth and the company’s competitiveness. The study employs a qualitative approach with the Design Thinking method, involving data collection through in-depth interviews and direct observations of consumers at Twenty-One Autos. The Design Thinking process is carried out through the Empathize, Define, Ideate, Prototype, and Testing phases. Through the Empathy stage, this research identifies various issues faced by consumers when purchasing used cars, including limited unit variations, complex credit processes, and suboptimal online shopping experiences. By analyzing the insights gained, the study formulates solutions to address these problems, such as adding unit variations, simplifying the credit process, and enhancing promotions and online sales to reach a wider audience. In the Ideate and Prototype stages, this research develops a digital platform that integrates various features to meet consumer needs, including unit variations, a simpler credit system, and more efficient online sales. Testing of this prototype shows that the implemented solutions are effective in improving sales conversions and customer satisfaction. The findings provide valuable insights into how consumer-based strategies can improve business operations, expand market share, and enhance the company’s competitiveness in the automotive industry.